Area-Restricted Search in Magellanic Woodpeckers: Importance of Tree Senescence, Forest Composition and Open Habitats [Konzentrierte Nahrungssuche Bei Magellanspechten: Die Bedeutung Von Baumalter, Waldzusammensetzung Und Offenhabitaten] - Vergara-Egert, P; Caro-Alarcon, D (Springer Science and Business Media Deutschland GmbH, 2021)
Animals with stable territories, specialized diets and narrow habitat choices, such as some woodpecker species, should concentrate foraging activity in areas of higher quality, a behavior consistent with the area-restricted search (ARS) behavior. The assessment of ARS behavior in specialized woodpeckers contributes to identify feeding areas important for not only their conservation but also habitats negatively affecting their foraging behavior. We addressed the effects of tree senescence, forest succession, stand composition and open habitats on the adoption of ARS behavior in Magellanic Woodpecker (Campephilus magellanicus) in a heterogeneous landscape in southern South America. Using GPS relocations from 24 woodpeckers, we estimated the First-Passage Time (FPT), a measure of the time individuals remain in a given area, with longer FPT values indicating the adoption of an ARS behavior. We determined the effects of habitat variables on FPT using a methodological framework based on Linear Mixed Effect models and a randomization procedure intended to reduce spatial autocorrelation. Averaged model coefficients showed that woodpeckers spent less time in sites dominated by the Antarctic beech (Nothofagus antarctica) and partially covered by open habitats. Conversely, FPT increased in stands and home ranges where tree senescence was higher. Thus, the ARS behavior in Magellanic Woodpecker is explained by forest composition, avoidance of open habitats and tree senescence. Our results suggest the conservation of Magellanic Woodpeckers in heterogeneous landscapes involves retention of senescent trees and maintenance of canopy continuity. © 2021, Deutsche Ornithologen-Gesellschaft e.V.